PELATIHAN PEMBUATAN SABUN DARI MINYAK JELANTAH SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT - Khofifah Tanjung; Putie Nurul Aina; Della R C P Sarumpaet; Asima br hutasoit; Siagian, Alexandra Marito; Gadis Apriani Manullang; Riskyana Damanik; Angri Nikita sari; Valentina Sinurat; Nur Hasanah Yugid Siregar; Sardi Pranata Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Used cooking oil is a household waste generated from daily cooking activities and has the potential to cause environmental pollution if not properly managed. This study aims to describe and analyze the implementation of training on making soap from used cooking oil as a community empowerment effort based on household waste management. The main problem underlying this study is the low level of public awareness and knowledge in managing used cooking oil, which can potentially cause negative impacts on the environment and health. On the other hand, used cooking oil has the potential to be processed into products with functional and economic value if managed properly.This study employs a descriptive qualitative approach with a case study design integrated into community service activities. The research subjects consist of community members, particularly housewives, who participated in the training on making soap from used cooking oil. Data collection techniques include observation, interviews, documentation, as well as pre-test and post-test evaluations. The data were analyzed using qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing.The results show that the training on making soap from used cooking oil significantly increased participants’ knowledge, skills, and environmental awareness. Participants not only understood the environmental impacts of used cooking oil but were also able to independently practice the soap-making process. In addition, the training activities provided potential economic added value through opportunities for developing household-based micro-enterprises. The training also encouraged the formation of participatory and collaborative attitudes among community members. Thus, training on making soap from used cooking oil can be used as a sustainable and applicable model of community empowerment. This study is expected to contribute to the development of community service programs and serve as a reference for policymakers in household waste management.